Headache Disorders May Be a Risk Factor for the Development of New Onset Hypothyroidism. Issue 1 (27th September 2016) - Martin, Andrew T.; Pinney, Susan M.; Xie, Changchun; Herrick, Robert L.; Bai, Yun; Buckholz, Jeanette; Martin, Vincent T.
Abstract : Objective: To determine whether headache disorders are a risk factor for the development of new onset hypothyroidism. Background: Past studies have reported associations between headache disorders and hypothyroidism, but the directionality of the association is unknown. Methods: This was a longitudinal retrospective cohort study using data from the Fernald Medical Monitoring Program (FMMP). Residents received physical examinations and thyroid function testing every 3 years during the 20 year program. Residents were excluded from the cohort if there was evidence of past thyroid disease or abnormal thyroid function tests at the first office visit. A diagnosis of a headache disorder was established by self‐report of "frequent headaches, " use of any headache‐specific medication, or a physician diagnosis of a headache disorder. The primary outcome measure was new onset hypothyroidism defined as the initiation of thyroid replacement therapy or TSH ≥ 10 without thyroid medication. A Cox survival analysis with time dependent variables were used for the model. Headache disorders, age, sex, body mass index, income, smoking, narcotic use, and hypothyroidism‐producing medications were independent variables in the model. Results: Data from 8412 residents enrolled in the FMMP were used in the current study. Headache disorders were present in about 26% of the residents and new onset hypothyroidism developed in ∼7%. The hazard ratio for the development of new onset hypothyroidism was 1.21 (95% CI = 1.001, 1.462) for those with headache disorders. Conclusions: Headache disorders may be associated with an increased risk for the development of new onset hypothyroidism.